2013
DOI: 10.1371/journal.pone.0061182
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of an Early Seroconversion to Simian Virus 40 in Healthy Children and Adolescents

Abstract: At present Simian virus 40 (SV40) infection in humans appears to be transmitted independently from early contaminated vaccines. In order to test the spread of SV40 infection in children, an immunologic assay employing specific SV40 synthetic peptides corresponding to its viral protein (VP) antigens was employed to estimate the seroprevalence of this polyomavirus in Italian infants and adolescents. Serum samples from 328 children and adolescents, up to 17 years, were investigated. Serum antibodies against SV40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(87 citation statements)
references
References 36 publications
6
81
0
Order By: Relevance
“…Molecular biology and immunological investigations reported on the presence of SV40 footprints in samples from healthy subjects and patients who had not administered with SV40-contaminated vaccines (24, 26). These studies indicate that the human-to-human contagion could be responsible of the SV40 infection in the human population.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biology and immunological investigations reported on the presence of SV40 footprints in samples from healthy subjects and patients who had not administered with SV40-contaminated vaccines (24, 26). These studies indicate that the human-to-human contagion could be responsible of the SV40 infection in the human population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous ELISA results indicated that the two SV40 peptides did not cross-react with the BKV and JCV hyperimmune sera that were employed as controls [20], [22]. The two peptides belong to the VP1/VP2/VP3 viral capsid proteins (VP1 ID: 1489598); VP3 ID: 9486895; web site, http://www.ncbi.nlm.nih.gov/nuccore).…”
Section: Methodsmentioning
confidence: 99%
“…BKV and JCV hyperimmune rabbit sera did not react with VP1 B or VP2/3 C peptides (negative control sera). The amino acid residues of the two specific SV40 VP peptides show low homology with the BKV, JCV and other polyomaviruses VPs [20], [22]. The characterization of these two peptides were published before [20], [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an indirect ELISA using synthetic peptides to SV40 capsid viral protein 1–3 epitopes has been utilized to screen healthy children and adolescents for exposure to SV40. 58 Results have indicated that; (i) SV40 infection is not widespread (16% prevalence of IgG antibody); (ii) IgM antibodies can be detected in 6–8 month old children, indicating that seroconversion can occur early in life; and (iii) that SV40 is circulating in the human population independent of SV40-contaminated vaccination. One caveat for this is that serological data for SV40 may be due to cross-reactivity to an, as yet undiscovered, human polyomavirus that is closely related to SV40.…”
Section: Kaposi Sarcoma-associated Herpesvirusmentioning
confidence: 99%